Audio and image encryption scheme based on QR decomposition and random modulus decomposition in Fresnel domain - Anjana, Savita; Yadav, Ak; Singh, Phool; Singh, Hukum (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
In this paper, an asymmetric audio and image encryption mechanism using QR decomposition and random modulus decomposition (RD) in the Fresnel domain is proposed. The audio file is recorded as a vector and converted to a two-dimensional array to act as an image or a sound map. This sound map is encrypted using the image encryption algorithm proposed in this paper. The proposed cryptosystem is validated for both audios and grayscale images. Fresnel parameters and the two private keys obtained from QR decomposition and random modulus decomposition (RD) form the key space. Computer-based reproductions have been carried out to prove the validity and authenticity of the scheme. Simulation results authenticate that the scheme is robust and efficient against various attacks and is sensitive to input parameters.
Optica Applicata, Vol. 52, 2022, nr 3, s. 359-374
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; QR decomposition; audio encryption; random modulus decomposition